From theory to practice: highlights from pharmacare 2026 - Mohd Fairol Anuar, Farisha; Rendrye, Nurul Ain Nadzirah; Ismail, Farhana Fakhira; Ibrahim, Norkasihan (Faculty of Pharmacy, 2026)
Pharmacare 2026, organised by the Society of Pharmacy Students (SOPHYS) was designed to provide a platform for students enrolled in the Community Pharmacy (PHC670) course to gain hands-on experience through social service and volunteerism. The initiative enabled participants to apply theoretical knowledge and professional skills in a real-world community setting while fostering empathy and a strong sense of professional responsibility.